Identifying the Learning Path of Online Learners in an Adaptive E-Learning Environment - Joseph, Lumy; Abraham, Sajimon (International Journal of Computer Sciences and Engineering, 2018)
With the advancement of technology, there is a rapid growth in e-learning. The use of the Internet in the teaching learning process has made significant impact on both teachers and students. Learners in an e-learning environment have different behavioural patterns, attitudes, aptitudes, learning styles, etc. and the learning resources preferred by these learners also vary. Hence, it is a big challenge for 21st century teachers to deliver the courses in an effective way. One solution to solve this problem is to provide an adaptive form of education. Advantage of this adaptive learning system is that it helps to provide apt material according to the interest and knowledge level of the learners or by understanding the learning facts. An adaptive learning system helps to track students’ knowledge, measure progress and provide solution accordingly. With the support of a suitable Learning Management System (LMS) it is possible to administer, track, report and document the delivery of e-learning courses. In this study, Moodle (Modular Object-Oriented Dynamic Learning Environment) LMS is used for managing every aspect of the course such as course creation, conducting online test, etc. In an e-learning environment, learning content accessed by individual learners will be different and they learn subjects at their own speed and interest. It causes the generation of different learning paths. Hence, the objective of the study is to develop a frame work for an adaptive learning system and identify the learning path of the learners based on their activities recorded in Moodle.